Empowering Early English Learning: Kindergarten Teachers’ Self-Efficacy and Instructional Strategies in Indonesia - Setya Putri Rahayu; Farida Noor Rohmah (VELES Voices of English Language Education Society, 2025)
Early exposure to English in Indonesia is increasingly recognized as a strategic foundation for children’s long-term linguistic and cognitive development. However, the inclusion of English at the kindergarten level remains non-mandatory and highly dependent on institutional readiness and teachers’ self-efficacy. This study investigates (1) how kindergarten teachers perceive their self-efficacy in integrating English as part of school activities, and (2) the efforts they undertake to insert English into classroom practices, particularly in schools where English is not part of the formal curriculum. Adopting a phenomenological qualitative design, data were collected through structured interviews and focus group discussions with 20 kindergarten teachers from three schools in Yogyakarta, Indonesia. The findings show that, while most teachers view early introduction to English as necessary to support children’s cognitive, communicative, and future academic development, their self-efficacy is constrained by limited language proficiency, insufficient training, and minimal institutional support. Teachers with longer experience demonstrated moderately stronger self-efficacy, whereas novice teachers expressed uncertainty due to the absence of systematic guidance. Despite these challenges, teachers showed initiative by incorporating simple vocabulary through multimodal activities such as songs, movement, printed visuals, and online resources—particularly TikTok—to sustain engagement. These practices, though creative, remain unstructured and highly individualized. Overall, the results highlight a paradox: teachers value early English learning but feel inadequately prepared to implement it effectively. Strengthening teachers’ self-efficacy through targeted professional development, structured pedagogical guidance, and supportive institutional environments is essential to improving the quality and consistency of early English education in Indonesia.